Mentoring the Development of Yellow Book Literacy Using the Halaqoh Method for Students at the Darunnajah Islamic Boarding School in Jakarta - Rokimin, Rokimin (Civiliza Publishing, 2024)
This study aims to enhance the literacy of kitab kuning among students at Darunnajah Islamic Boarding School Jakarta through the implementation of the halaqah method. The halaqah method was chosen because it is believed to create an interactive and conducive learning atmosphere for mastering kitab kuning material. This research uses a mixed-methods approach, combining both qualitative and quantitative methods. The qualitative approach is used to understand the process of implementing the halaqah method, while the quantitative approach is used to measure the improvement in kitab kuning literacy. Qualitative data were collected through observations and in-depth interviews with students and teachers, while quantitative data were obtained through written tests before and after the implementation of the halaqah method. The results show that the implementation of the halaqah method significantly improves students' understanding of kitab kuning literacy. This improvement is evident in the higher test scores and increased ability of students to read and comprehend kitab kuning texts. Additionally, the halaqah method also enhanced student engagement and motivation in the learning process. These findings indicate that the halaqah method can be an effective alternative for developing kitab kuning literacy in Islamic boarding schools.